Performance analysis of 6 Slot 8 Pole permanent magnet linear mot - Abdul Shukor, Fairul Azhar; Misron, Norhisam; Wakiwaka, Hiroyuki; Tashiro, Kunihisa; Nirei , Masami (MTUN UTeM, 2013)
Currently, palm oil is the most consumed vegetable oil in the world. Therefore, an increment in its productivity is essential to ensure its sustainability in the market. One option is through the mechanization of the tools used to harvest it. In this paper, the design of the actuator for mechanized oil palm harvesting tools was discussed. A 3 phase permanent magnet linear motor with a 6 slot 8 pole structure topology known as 3PhSTLOA was used as the actuator structure. The structure of 3PhSTLOA has been optimized. The aim of the optimization is to allow the 3PhSTLOA to produce at least 200 N of average thrust at a total weight of under 2.0 kg. As a result of optimizing the 3PhSTLOA produced about 202 N of average thrust at 1.8 kg of its total weight. The performance of 3PhSTLOA is then compared with the previous type of actuator in mechanized harvesting tools.